Penerapan Akuntansi Mudharabah Pada Perusahaan - Hasibuan, Ade Lia Syafitri; Yarham, M. (Universitas Muhammadiyah Sumatera Utara, 2023)
This research focuses on the application of mudharabah accounting in companies based on PSAK No. 105. The issues raised are how large companies apply mudharabah accounting in their respective Financial Institutions, understanding mudharabah and affirmation from the sources of the Qur'an and Hadith in profit taking. The method used is qualitative research method, Furthermore, qualitative research is a process of discovery and understanding based on methodology. In this approach, researchers paint a complex picture, examine books and detailed reports on views. Qualitative research is an attempt to present the social world, and its view of the world, in terms of concepts, behavior, perceptions, and issues about the people studied.